Ikhtisar perkembangan sistem bagi-hasil di Indonesia secara historis dan geografis 2 - SCHELTEMA, A.M.PA. ([Tidak Terdaftar], 1980)
Ikhtisar perkembangan sistem bagi-hasil di Indonesia secara historis dan geografis 2